Promising traditional Indian medicinal plants for the management of novel Coronavirus disease: A systematic review. (16th June 2021) - Singh, Rahul Soloman; Singh, Ashutosh; Kaur, Harpinder; Batra, Gitika; Sarma, Phulen; Kaur, Hardeep; Bhattacharyya, Anusuya; Sharma, Amit Raj; Kumar, Subodh; Upadhyay, Sujata; Tiwari, Vinod; Avti, Pramod; et al.
Abstract : Traditional Indian medical practices (Ayurveda, Siddha, Unani, and homeopathy) are a vast reservoir of knowledge about medicinal plants. The promising pharmacological properties of these plants have paved the way for developing therapy against novel Coronavirus (CoV) infection. The current review will summarize published works of literature on the effects of traditional Indian medicinal plants against acute respiratory infection (COVID‐19, SARS, Influenza, and Respiratory syncytial virus infection) and registered clinical trials of traditional Indian herbal medicines in COVID‐19. The current study aims to comprehensively evaluate the data of traditional Indian medicinal plants to warrant their use in COVID‐19 management. PubMed, Embase, and Cochrane databases were searched along with different clinical trial databases. A total of 22 relevant traditional Indian medicinal plants (35 relevant studies) were included in the current study having potential antiviral properties against virus‐induced respiratory illness along with promising immunomodulatory and thrombolytic properties. Further, 36 randomized and nonrandomized registered clinical trials were also included that were aimed at evaluating the efficacy of herbal plants or their formulations in COVID‐19 management. The antiviral, immunomodulatory, and thrombolytic activities of the traditional Indian medicinal plants laid down a strong rationale for their use in developing therapies against SARS‐CoV‐2 infection. The study identified some important potential traditional Indian medicinal herbs such as Ocimum tenuiflorum, Tinospora cordifolia, Achyranthes bidentata, Cinnamomum cassia, Cydonia oblonga, Embelin ribes, Justicia adhatoda, Momordica charantia, Withania somnifera, Zingiber officinale, Camphor, and Kabusura kudineer, which could be used in therapeutic strategies against SARS‐CoV‐2 infection.